2015
DOI: 10.1093/isq/sqv003
|View full text |Cite
|
Sign up to set email alerts
|

Oil and International Cooperation

Abstract: The more that states depend on oil exports, the less cooperative they become: they grow less likely to join intergovernmental organizations, to accept the compulsory jurisdiction of international judicial bodies, and to agree to binding arbitration for investment disputes. This pattern is robust to the use of country and year fixed effects, to alternative measures of the key variables, and to the exclusion of all countries in the Middle East. To explain this pattern, we consider the economic incentives that fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 75 publications
2
18
0
Order By: Relevance
“…23 States with large endowments of oil wealth perform systematically worse in respecting human rights (DeMeritt and Young, 2013). Moreover, there is an emerging body of evidence that oil producer status exerts powerful effects on those countries’ international affairs as well, suppressing participation in institutions of global governance (Ross and Voeten, 2015) and, when combined with revolutionary, revisionist ambitions, making them more conflict-prone (Colgan, 2010, 2013). However, our knowledge of how oil prices affect interstate behavior is comparatively scant, since these studies do not explicitly incorporate price effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 States with large endowments of oil wealth perform systematically worse in respecting human rights (DeMeritt and Young, 2013). Moreover, there is an emerging body of evidence that oil producer status exerts powerful effects on those countries’ international affairs as well, suppressing participation in institutions of global governance (Ross and Voeten, 2015) and, when combined with revolutionary, revisionist ambitions, making them more conflict-prone (Colgan, 2010, 2013). However, our knowledge of how oil prices affect interstate behavior is comparatively scant, since these studies do not explicitly incorporate price effects.…”
Section: Discussionmentioning
confidence: 99%
“…Even if these expenditures are driven by a desire to enhance defensive capacity, the fungibility of most military assets makes their amassment by one country an inherent menace to its neighbors (Jervis, 1977). While this menace can be mitigated through credible signaling of defensive intent (Fearon, 1997; Lake, 1992), said signaling is more difficult for many oil-exporting states, which are less democratic (Andersen and Ross, 2014) and less well integrated in global governance institutions (Ross and Voeten, 2015). Democratic institutions contribute to peace by overcoming the information asymmetry problems inherent to crisis bargaining (Schultz, 1998) and joint membership in international institutions suppresses conflict by conveying credible information of intent, socializing states into appropriate norms of behavior, and providing venues for bargaining and problem solving (Russett et al, 1998).…”
Section: Theory: Oil Exporters and Conflict Behaviormentioning
confidence: 99%
“…New technologies such as fracking and renewable energy constantly disrupt global energy trade and transform interstate relations. Specific case studies examining how states shape their foreign policy to ensure energy security (Kalicki and Glodwyn, 2005;Daijong, 2006;Krickovic, 2015), have led to further studies that systematically correlate energy attributes of a single state to its foreign policy actions (Colgan, 2011;Ross and Voeten, 2015). More recently, scholars have started looking at how energy shapes relations between two states.…”
Section: Renewables and Energy Trade: A New Form Of Interdependence?mentioning
confidence: 99%
“…' Michael Ross (2012) has demonstrated that rents from natural resources (and oil in particular) weaken state institutions in producer states, leading to economic instability and a higher incidence of civil conflict. Similarly, Ross and Voeten (2015) showed that "natural wealth liberates states from the economic pressures that would otherwise drive them toward [international] cooperation." Since there is often an asymmetric relationship between energy exporters and the importers (Goldthau 2008;Harsem and Claes 2013), suppliers often resort to using energy as a foreign policy tool (Smith 2008;Kramer 2009).…”
Section: Energy and Quantitative Political Science: Taking Stockmentioning
confidence: 99%